Gram-scale production of nitrogen doped graphene using a 1, 3-dipolar organic precursor and its utilisation as a stable, metal free oxygen evolution reaction catalyst. Issue 55 (26th June 2017) - Bayazit, Mustafa K.; Moniz, Savio J. A.; Coleman, Karl S.
Abstract : For the first time, a one-step scalable synthesis of a few-layer ∼10% nitrogen doped (N-doped) graphene nanosheets (GNSs) from a stable but highly reactive 1, 3-dipolar organic precursor is reported. Abstract : For the first time, a one-step scalable synthesis of a few-layer ∼10% nitrogen doped (N-doped) graphene nanosheets (GNSs) from a stable but highly reactive 1, 3-dipolar organic precursor is reported. The utilization of these N-doped GNSs as metal-free electrocatalysts for the oxygen evolution reaction (OER) is also demonstrated. This process may open the path for the scalable production of other heteroatom doped GNSs by using the broad library of well-known, stable 1, 3-dipolar organic compounds.